2006
DOI: 10.3748/wjg.v12.i41.6702
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotypes in chronic liver disease patients from New Delhi, India

Abstract: Only HBV genotypes A and D were present in patients with CLDB from New Delhi, India. Compared with genotype D, genotype A patients had no significant clinical or biochemical differences (P>0.05). Mixed infection with genotype A and D were seen in 3% of the cases. Genotype D was the dominant genotype prevalent in all patient categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 16 publications
6
34
0
Order By: Relevance
“…But, we did not observe genotype E in our population as the study of Singh et al, 23 in accordance with the study of Kar et al 24 Chattopadhyay et al 25 reported predominance of genotype D followed by genotype A among patients with chronic liver disease from New Delhi.…”
Section: Conflicts Of Interestsupporting
confidence: 86%
“…But, we did not observe genotype E in our population as the study of Singh et al, 23 in accordance with the study of Kar et al 24 Chattopadhyay et al 25 reported predominance of genotype D followed by genotype A among patients with chronic liver disease from New Delhi.…”
Section: Conflicts Of Interestsupporting
confidence: 86%
“…We and others from India have reported the presence of mixed genotype A and D [9][10][11][12] . However, despite the presence of mixed genotypes, there are no reports from India about the presence of recombination, especially using the full-length HBV genome sequencing approach.…”
Section: H E P a T I T I S B V I R U S ( H Bmentioning
confidence: 56%
“…10 But the traditional restriction fragment length polymorphism (RFLP) methods can identify only genotypes A-F. Zeng et al 11 carried out an RFLP using digestion of enzymes BsrI, StyI, DpnI, HpaII, and EaeI, in 240 HBV S gene isolates (obtained from GeneBank) and demonstrated all eight genotypes. Chattopadhyay et al 12 demonstrated the RFLP and PCR using type-specific primers for genotyping agreed well with sequencing among 100 HBV-DNApositive North Indian patients.…”
Section: Restriction Fragment Length Polymorphismmentioning
confidence: 85%